Situation Report: Hungary, 24 April 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Western Bank Loan for Hungarian Aluminum Enterprise New Licenses for Private Retail Traders, New Permits for Private Artisans More "Gastarbeiter" to the GDR Hungarian-Ukrainian Scientific Cooperation Automobile Imports MTI Correspondent Expelled from China The Importance of and Problems in Cattle Breeding